Professional competencies for sustainable transformation - Ansmann, Moritz [Verfasser]; Schwarz, Maria [Verfasser]; Melzig, Christian [Verfasser]; Hemkes, Barbara [Verfasser] (My University, 2024)
„Climate change, species extinction and the unequal distribution of finite resources require a shift of paradigm in Vocational Education and Training (VET). VET has the responsibility to promote competencies that are necessary for advancing and helping to shape the sustainable transformation. The BIBB (German Federal Institute of Vocational Training) is addressing this with the corresponding modernisation of training regulations, but also with the promotion of pilot projects. Pilot Projects are collaborative projects between universities, research institutions, companies, and industry associations aimed at developing and testing practical innovations for vocational education and training. The article presents core findings and highlights the role of training personnel in the integration of sustainability in VET.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; S 2.3.1 Modellversuche in der Berufsbildung; P 3.2.1 Ausbilder; 370; Berufsbildung; Nachhaltige Entwicklung; Kompetenzentwicklung; Ausbilder; Modellversuch; Bundesinstitut für Berufsbildung